Pengaruh Pemberian Pupuk Kandang dan Mikoriza terhadap Pertumbuhan Tanaman Kelapa Sawit (Elaeis guineensis Jacq.) di Pembibitan Pre-Nursery - Lubis, Yan Hariadi; Panggabean, Ellen Lumisar; Azhari, Azhari (Universitas Medan Area, 2019)
In the Indonesian economy, the oil palm commodity plays a pretty bright role because it serves as a source of foreign exchange. The need to develop technology in producing superior seeds. In this study discuss about the Influence of Giving Fertilizer and Mikoriza Against the Growth of Palm Oil Plants (Elaeis guineensis jacq.) In Pre-Nursery Nursery. This study aims to determine the effect of manure and mycorrhizal fertilization as well as its interaction on the growth of coconut plants in pre-nursery nurseries. The study was designed by Factorial Randomized Block Design consisting of 2 treatment factors. The first factor of treatment of manure (K) consisting of 4 levels, namely: K0 = 0 kg / polybag, K1 = 0.15 kg / polybag, K2 = 0.30 kg / polybag, and K3 = 0.45 kg/polybag. The second factor of mycorrhizal treatment (M) consisting of 4 levels, namely: M1 = 12.5 g/polybag, M2 = 25.0 g/polybag, M3 = 37.5 g / polybag. The results showed that the treatment of cow manure up to 0.45 kg/polybag can increase the height of seedlings, stem diameter, total leaf area, wet weight of seedlings and dry weight of seedlings, but did not affect the number of oil palm seedlings.Mikoriza treatment up to 37, 5 g / polybags can increase seed height, stem diameter, total leaf area, wet weight of seedlings and dry weight of seedlings, but have no significant effect on the number of oil palm seedlings. The interaction between cow manure and mycorrhiza had no effect on all parameters observed.